Treatment of Gastric Cancer Patients During COVID-19 Pandemic: The West is More Vulnerable - Polkowski WP; Sędłak K; Rawicz-Pruszyński K (Cancer Management and Research, 2020)
Wojciech Piotr Polkowski, Katarzyna Sędłak, Karol Rawicz-Pruszyński Department of Surgical Oncology, Medical University of Lublin, Lublin, PolandCorrespondence: Wojciech Piotr PolkowskiDepartment of Surgical Oncology, Medical University of Lublin, Radziwiłłowska 13 St, Lublin 20-080, PolandTel +48 81 531 81 25Fax +48 81 531 81 33Email wojciech.polkowski@uml.edu.plAbstract: The outbreak of the COVID-19 is currently the biggest international concern. Treatment of gastric cancer (GC) patients in the pandemic era with high hospital burden and under severe oncological/surgical resource constraints should implicate a need for resource re-allocation with a new “pandemic” GC treatment algorithm. The neoadjuvant/perioperative (radio-)chemotherapy is applied in the majority of advanced GC cases with poor postoperative therapy compliance. In the East, radical surgery is frequently used in the first instance, with adjuvant chemotherapy reserved for patients with a high risk of recurrence. Moreover, the elderly population might be effectively treated by surgery alone, thus saving oncological resources for younger people who need a more aggressive approach. In this framework, prioritization is a key concept based on the severity of symptoms and the need for urgent (surgical) intervention. High-risk and marginally effective surgery should be replaced with definitive radio- and/or chemotherapy. The pandemic framework to provide optimal care for GC patients must be based on multidisciplinary decision-making and include all anti-cancer treatment options: surgery, systemic therapy, and radiotherapy. The priority and staffing dictate adherence to the new algorithm. We believe that these priorities may improve the delivery of care to all, including elderly GC patients.Keywords: COVID-19, gastric cancer, multidisciplinary treatment